Security protection using Simple Object Access Protocol (SOAP) messages techniques - Ghossoon, Mohammed Waleed Al-Saadoon; R. Badlishah, Ahmad (Institute of Electrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org